A new thickness-based accelerated aging test methodology for resin materials: Theory and preliminary experimental study. (20th October 2018) - Wang, Yanlei; Zhang, Xue; Cai, Gaochuang; Wan, Baolin; Waldmann, Danièle; Qu, Yuan
Highlights: Thickness-based accelerated aging test method (ThAM) is firstly proposed for resin materials. Acceleration factors are theoretically deduced for water absorption and tensile behaviours of resin materials. Effects of specimen thickness on water absorption and tensile strength retention of resin materials are studied. The proposed ThAM ensures stable accelerated efficiency without changing the degradation mechanism of resin materials. Abstract: This paper proposes a novel accelerated test method based on the thickness of resin materials. This method is to overcome the adverse influence of high temperature on the reliability of experimental results of the accelerated tests widely adopted in the current practice. To verify the proposed thickness-based accelerated method (ThAM), an experimental investigation was conducted focusing on the water absorption and tensile properties of epoxy resin. The results suggest that the existing temperature-based accelerated method (TAM) cannot be applied when the test temperature is high as in this case the degradation mechanism of materials is probably changed. The acceleration factor of TAM is greatly dependent on the type of test solution, which further limits the application in the accelerated test. Compared with TAM, the new method is much easier to apply, and more stable and reasonable to accelerate the aging test of epoxy resin.